Prevalence and characteristics of gastrointestinal disorders, medication use, and diagnostic interventions in pediatric patients with cystic fibrosis: a nested case–control analysis from the TriNetX EMR-derived global research network real-world dataset - Trocchia, Carolena; Mosha, Maua; Hamner, Bailey; Goldenberg, Neil; Khalaf, Racha (Frontiers in Gastroenterology, 2025)
BackgroundGastrointestinal (GI) disease in pediatric patients with cystic fibrosis (CF) is a growing concern in the era of improved lung disease; however, the true prevalence of GI diagnoses, medical therapies, and frequency of diagnostic and therapeutic interventions in this population have yet to be explored on a multisystem scale. The aim of the present study was to describe, among pediatric patients with CF (PwCF) compared to a large cohort of healthy controls, the prevalence and types of 1) GI disorders; 2) GI medication use; and 3) GI procedural interventions. MethodsThis was a multicenter case-control analysis using the TriNetX electronic medical record (EMR) global anonymized data platform. Patients were included if they had an ICD9/10 diagnosis code and were between the age of zero to ≤ 21 years between January 1st, 2010, and January 1st, 2020. Those with a history of solid organ transplants were excluded.ResultsThe cohort was comprised of 7,649 patients with a diagnosis of CF (cases) and 22,516,240 patients without CF (controls). The prevalence of any GI disorder was greater in pediatric PwCF compared to those without CF (73% versus <1%). The prevalence of diseases of the biliary tract and pancreas (43% vs. <1%; p<.0001), hepatic disease (8.8% vs. <1%; p<.0001), disease of the esophagus to duodenum (34% vs. <1%; p<.0001), and intestinal disease (43% vs. <1%; p<.0001) were each significantly greater in PwCF (p<0.0001). Furthermore, the frequencies of esophagogastroduodenoscopy (EGD), colonoscopy and endoscopic retrograde cholangiopancreatography (ERCP) were significantly higher among PwCF than controls (9.5% vs. <1%; 2.8%% vs. <1%; and 0.3% vs <.001% respectively; p<0.0001 for all comparisons). ConclusionThe prevalence of GI diagnoses, use of GI medications, and frequency of GI procedures are all higher among pediatric patients PwCF. Prospective multicenter studies are warranted to substantiate these findings, further investigate risk factors for GI disorders, and to describe potential changes in GI disorders with novel CF disease-modifying therapies.